Tumor blood flow modifying effects of electrochemotherapy - Serša, Gregor (Radiology and oncology (Ljubljana), 2003)
Background. The aim of this study was to determine the tumor blood flow modifying, and potential vascular targeted effect of electrochemotherapy with bleomycin or cisplatin. Materials and methods. Electrochemotherapy was performed by application of short intense electric pulses to the tumors after systemic administration of bleomycin or cisplatin. Evaluated were antitumor effectiveness of electrochemotherapy by tumor measurement, tumor blood flow modifying effect by Patent blue staining technique, and sensitivity of endothelial and tumor cells to the drugs and electrochemotherapy by clonogenicity assay. Results. Electrochemotherapy was effective in treatment of SA-1 tumors in A/J mice resulting in substantial tumor growth delay and also tumor cures. Tumor blood flow reduction following electrochemotherapy correlated well with its antitumor effectiveness. Virtually complete shut downof the tumor blood flow was observed already at 24 h after electrochemotherapy with bleomycin whereas only 50% reduction was observed after electrochemotherapy with cisplatin. Sensitivity of human endothelial HMEC-1 cells to electrochemotherapy suggests a vascular targeted effect for electrochemotherapy in vivo with bleomycin as well as with cisplatin. Conclusion. These results show that in addition to direct electroporation of tumor cells, other vascular targeted mechanisms are involved in electrochemotherapy with bleomycin or cisplatin, potentially mediated by tumorblood flow reduction, and enhanced tumor cell death as a result of endothelial damage by electrochemotherapy.
Keywords: Bleomicin; Bleomycin; Blood Supply; Cisplatin; Drug Delivery Systems; Drug Therapy; Electroporation; elektrokemoterapija; Elektroporacija; Mice; Miši; neoplasm; Sarcoma, Experimental; Sarkom eksperimentalni; Therapy; tumor; Zdravilo, sproščanje, sistemi; zdravljenje